2015
DOI: 10.1002/ep.12178
|View full text |Cite
|
Sign up to set email alerts
|

The impact of capacity and location of multidistributed generator integrated in the distribution system on electrical line losses, reliability, and interruption cost

Abstract: The primary purpose of this article is to study the impact of distributed generator (DG) integrated into the distribution system in terms of electrical line losses, reliability and interruption cost. The single‐ and multi‐distributed generators (DG) under this study are connected to a 22 kV distribution system of the Provincial Electricity Authority (PEA) that is a part of Thailand's distribution system. Geographic information systems data, including the lengths of the distribution line and the load locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that the presence of a DG system in the network has several advantages for distribution systems [13], such as an improvement in voltage stability [14], power quality [15,16], power loss reduction [17][18][19], and reactive power compensation [20]. In terms of system reliability, research has shown that optimal DG placement can improve the System Average Interruption Frequency Index and the System Average Interruption Duration Index in a distribution system [21]. The power system's reliability can also be improved when the DG system is located in a suitable location, which can benefit the utility and the customer from an economic perspective [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the presence of a DG system in the network has several advantages for distribution systems [13], such as an improvement in voltage stability [14], power quality [15,16], power loss reduction [17][18][19], and reactive power compensation [20]. In terms of system reliability, research has shown that optimal DG placement can improve the System Average Interruption Frequency Index and the System Average Interruption Duration Index in a distribution system [21]. The power system's reliability can also be improved when the DG system is located in a suitable location, which can benefit the utility and the customer from an economic perspective [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Simple protective devices are proposed and utilised on the radial distribution system, such as the overcurrent [6][7][8], reclosers [9,10], and fuses [11,12]. Losses of coordinated protective devices are concerned with the processes observed, such as loss of tripping, loss of action, and loss of trip command to another device [13,14]. However, the protection characteristics are applied to the distribution system, in which the operation has to be correctly performed and perfectly functional as per the conceptual providing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the randomness and volatility of new energy power could cause more complex grid loss mechanisms and loss reduction problems [20]. References [21][22][23] analyzed the impact of DG access capacity and access location on distribution network line losses. The traditional line loss calculation method has some limitations in calculating the line loss for distributed networks with DGs.…”
Section: Introductionmentioning
confidence: 99%